Thionation of Aminophthalimide Hindered Carbonyl Groups and Application to the Synthesis of 3,6′-Dithionated Pomalidomides - Scerba, Michael T.; Siegler, Maxime A.; Greig, Nigel H. (Synlett, 2021)
Herein, we present a new one-pot procedure for the 3,6′-dithionation of pomalidomide derivatives in which the key 3-position sulfur atom is preferentially installed at the desired (but sterically congested) carbonyl of the aminophthalimide system and with regiochemistry distinct from Lawesson’s Reagent thionation methods. When heated in 1,4-dioxane with P4S10–pyridine complex, pomalidomides are smoothly and reproducibly converted into their 3,6′-dithionated analogues in roughly 30% isolated yield and at various scales. While detrimental to the desired 3,6′-type outcome when employing Lawesson’s Reagent, we hypothesize that the pomalidomide aniline group instead facilitates P4S10-type thionation at the otherwise hindered 3-position carbonyl, contributing to the selectivity observed. When paired with classical methods of thionation, this approach offers an interesting and appealing addition to the synthetic toolbox, permitting facile late-stage access to complementary thionated pomalidomides in direct single-flask procedures.
Keywords: thionation; pomalidomides; dithionation; aminophthalimides; regioselectivity